2006
DOI: 10.1097/01.ta.0000223463.88422.6a
|View full text |Cite
|
Sign up to set email alerts
|

Vital Capacity as a Predictor of Outcome in Elderly Patients with Rib Fractures

Abstract: Bedside VC is a simple measurement which could predict LOS in elderly patients with rib fractures and may identify those patients requiring ECF upon discharge. Further prospective study may highlight the utility of emergency room VC in determining the disposition of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 17 publications
0
52
0
Order By: Relevance
“…Evidence suggests that treatment algorithms can be stratified based on patient age, number of RFs, and admission vital capacity. 32 In conclusion, a large regional trauma cooperative confirmed that older age and increased ISS are independent predictors of survival in older patients incurring traumatic RFs. Contributing to mortality were CHF, intubation, and admission to high-volume trauma centers.…”
Section: Commentmentioning
confidence: 61%
“…Evidence suggests that treatment algorithms can be stratified based on patient age, number of RFs, and admission vital capacity. 32 In conclusion, a large regional trauma cooperative confirmed that older age and increased ISS are independent predictors of survival in older patients incurring traumatic RFs. Contributing to mortality were CHF, intubation, and admission to high-volume trauma centers.…”
Section: Commentmentioning
confidence: 61%
“…Table 1 summarizes the characteristics of the 13 included studies representing a total of 79,313 patients. [14][15][16][17][18][19][20][21][22][23][24][25][26] Studies were published between 1985 and 2016; 11 studies were performed in the United States, [14][15][16][17][20][21][22][23][24][25][26] 1 was performed in Egypt, 19 and 1 was performed in Israel. 18 All 13 were retrospective cohort studies, with the majority using data from trauma registries.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19]21,25,26 Eight studies included morbidity as a primary outcome of interest. [14][15][16][18][19][20]22,23 Six studies examined prognostic factors related to LOS. [14][15][16]22,[24][25][26] One study examined prognostic factors related to discharge to an extended care facility.…”
Section: Resultsmentioning
confidence: 99%
“…33 The severity is directly related to a defect of the ventilatory system, because FVC could predict the duration of stay in elderly patients with rib fractures. 34 In our cohort, we included only multiple trauma patients who survived after discharge from the ICU. Because of these inclusion criteria, only three patients were older than 60 yr.…”
Section: Discussionmentioning
confidence: 99%